Mutu sensorik dan kandungan protein kue kering tepung ikan gabus (Channa striata) - Novianty; Zairinayati; Suzanna, Ema (IKesT Muhammadiyah Palembang, 2026)
Background: Cookies are cookies made from small-sized wheat flour, have a sweet taste, dense and crunchy texture. Cookies are made from low-protein flour. The protein content comes from a mixture of margarine and flour in small amounts, therefore it is necessary to make modifications in the form of protein fortification from other sources, one of which is snakehead fish flour. Research Objective: to analyze the sensory quality and protein content of snakehead fish flour cookies (Chana striata). Research Method: The method used in the study is an experimental method with a non-factorial Completely Randomized Design (CRD). Treatment. Treatment of the ratio of snakehead fish flour and wheat flour in making cookies, namely P1 0% (snakehead fish flour): 100% (wheat flour), P2 25% (snakehead fish flour): 75% (wheat flour), P3 30% (snakehead fish flour): 70% (wheat flour). Results: The analysis results showed that there were significant differences in sensory quality with a comparison of each treatment and there were significant differences in protein content with a comparison of each treatment. Conclusion: The control formulation (P0) was 65.4 and the highest protein content was in the 25% formula (P2) at 15.13%.